THE IDEA OF PROGRESSION IN DESIGNING THE CURRICULUM OF ROMANIAN AS A FOREIGN LANGUAGE (RFL) - PLATON, Elena (Studia Universitatis Babeș-Bolyai Philologia, 2019)
The idea of progression in designing the curriculum of Romanian as a foreign language (RFL). Although it constitutes a constant reality in teaching foreign languages and, even more, in the process of designing the curriculum, the idea of progression has been, in turn, glorified, marginalised or even crucified by didacticians, especially during the heyday of the communicative methods and the action-perspective on teaching. Lately, the theoretical debates from the outside medium have been trying to rehabilitate it, starting from the idea that a natural language is, practically, infinite and that, in the didactic context, it is required to find an “end” in order to establish accurately the fundamental reference points for a teaching-learning-evaluating path that is as efficient as possible. In the case of the RFL, grammatical progression has remained a central point of interest for specialists for over three decades. However, the echoes of communicative methods, though perceptively diminished in intensity in the Western world, have lately determined them to increasingly favour communicativeness and authenticity, at least at the declarative level, considering that in this way they will guarantee the “modernity” of the discourse. Yet, the resurrection of enthusiasm for the two concepts has sometimes led to exaggerated attitudes that disapproved of the proposals of progressive description and organisation of the teaching contents, because of too rigid and inadequate an understanding of the notion of progression. In our study, we intend to sensitise Romanian specialists to the need of looking at the idea of progression with more flexibility, without which designing a didactic process that is coherently articulated is inconceivable, especially in the first stages of RFL acquisition and, especially, when one does not resort to any other contact language while teaching it. REZUMAT. Ideea de progresie în proiectarea curriculară a limbii române ca limbă străină (RLS). Deși constituie o realitate mereu prezentă în practica predării limbilor străine și, cu atât mai mult, în procesul de proiectare curriculară, ideea de progresie a fost, rând pe rând, glorificată, marginalizată sau chiar crucificată de către didacticieni, mai ales în perioada de vârf a metodelor comunicative și a perspectivei acționale asupra predării. În ultimul timp, dezbaterile teoretice din mediul extern încearcă să o reabiliteze, pornind de la ideea că limba naturală este, practic, infinită, și că, în context didactic, se impune găsirea unui „capăt” pentru a putea stabili cu precizie reperele fundamentale ale unui parcurs cât mai eficient de predare-învățare-evaluare. În cazul RLS, progresia gramaticală a rămas vreme de mai bine de trei decenii principalul centru de interes al specialiștilor. Însă, în ultimii ani, ecourile metodelor comunicative, deja sensibil atenuate în intensitate în lumea apuseană, i-au determinat să privilegieze tot mai mult comunicativul și autenticitatea, cel puțin la nivel declarativ, considerând că, astfel, vor avea asigurată „modernitatea” discursului. Reînvierea entuziasmului pentru cele două concepte a condus însă, uneori, la atitudini exagerate, care dezaprobau propunerile de descriere și de ordonare progresivă a conținuturilor de predat, din cauza unei înțelegeri prea rigide și inadecvate a noțiunii de progresie. În studiul nostru, ne propunem să sensibilizăm specialiștii români în legătură cu nevoia de a privi cu mai multă flexibilitate ideea de progresie, fără de care este de neconceput proiectarea unui parcurs didactic coerent articulat, mai ales în primele stadii de achiziție a RLS și, în special, atunci când nu se apelează la nicio limbă de contact pentru predarea acesteia. Cuvinte-cheie: româna ca limbă străină, progresie, macroprogresie, microprogresie, interlimbă, microlimbă, input, intake, output, curriculum.